Law against attempted suicide in Malaysia: comparative studies with United Kingdom and India / Farah Adibah Azmi … [et al.] - Azmi, Farah Adibah; Ismail, Isma Afira; Baharon, Najihah; Redzuan, Nur Fatin Izzaty (2013)
The research is carried out to analyse the comprehensiveness of Malaysia's Penal Code in relation to its provision regarding the offence of an attempted suicide which is section 309 of the Act. The research will focus on the relevancy of the criminalisation of attempted suicide by evaluating the punishment imposed under such provision and its implications. In order to have better assessment on its comprehensiveness, comparative studies with the law in other countries namely United Kingdom, and Canada which are no longer enforcing the law against attempted suicide, and together with India and Singapore which are still criminalising attempted suicide were also conducted. The research is based on qualitative type of research by focusing on data gathered from various written sources as well as interviews conducted with legal experts. Taking all the given parameters into consideration, and on the basis of the legal analyses, the research concludes that the act of attempted suicide should no longer be criminalised.